Women corporate board members and stock performance - Guo, Joanne (International Journal of Scientific Research and Management (IJSRM), 2024)
The increasing presence of women in corporate boards is now taking central stage in discussions related to corporate governance and performance. There have been those who point at enhancements in decision-making, governance, and overall firm performance due to gender diversity, though others question its financial benefit directly. This literature review appraises empirical studies and theoretical frameworks concerning women's representation on boards and their consequences for corporate outcomes. It examines global developments, particularly in Europe and North America, across topics ranging from the impact of gender quotas to voluntary diversity initiatives and the challenges women face in ascending into positions in corporate leadership. The review also discusses the non-economic benefits of gender diversity, such as improvements in levels of corporate social responsibility and enhancement of corporate reputation. The findings indicate that, while there is evidence supporting the positive outcomes of board diversity, results are context-dependent and further research is needed to assess long-term and cross-industry impacts. With this review, an attempt is made to contribute to a deeper understanding of the complex relation between gender diversity and corporate performance. Additionally, the paper offers some recommendations for policymakers and corporations in their efforts to foster diversity.